Genetic Diversity of Local Maize Germplasm of Tana Toraja South Sulawesi Using SSR (Simple Sequence Repeat) Markers - Ramlah Ramlah; Isna Rasdianah Aziz; Cut Muthiadin; Mashuri Masri; Muhammad Khalifah Mustami; Marcia Bunga Pabendon (Faculty of Agriculture, Universitas Gadjah Mada jointly with PISPI, 2017)
Plant genetic diversity is an emerging variation in a crop group caused by its genetic factors. Local corn germplasm as a source of plant genes that are able to adapt to the local environment. The purpose of this research is to obtain information on genetic variation of Tana Toraja local maize germ plasm using SSR (Simple Sequence Repeat) marker. This research was conducted at Balitsereal Molecular Biology Laboratory, Agricultural Research Agency in Maros Regency, South Sulawesi. A total of 4 local maize populations were analyzed by laboratory experimental method with observation with NTSYS pc 2.1 program. The results showed that the average number of alleles was 3.72 alleles per locus and the polymorphism rate of 0.53 with the genetic similarity coefficient was in the range of 0.47 to 0.85. 2 main clusters formed in the genetic similarity coefficient 0.47. Klaster I is Local DallePondan and Local Purple. Klaster II is Local Bebo and Kandora. The genetic distance is in the range of 0.15 to 0.74 with an average genetic distance of 0.46. From the data obtained shows that the 4th germplasm of the population of Tana Toraja Local maize diteleti has a very informative level of genetic diversity. Genetic diversity of local maize germplasm of Tana Toraja, can be used as a source of genes in the assembly of improved varieties in the future.